2018
DOI: 10.1016/j.celrep.2018.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Condition-Dependent Neural Dimensions Progressively Shift during Reach to Grasp

Abstract: SUMMARY Neural population space analysis was performed to assess the dimensionality and dynamics of the neural population in the primary motor cortex (M1) during a reach-grasp-manipulation task in which both the reach location and the object being grasped were varied. We partitioned neural activity into three components: (1) general task-related activity independent of location and object, (2) location- and/or object-related activity, and (3) noise. Neural modulation related to location and/or object was only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 56 publications
7
44
1
Order By: Relevance
“…The changes in motor cortical maps were not accompanied by corresponding changes in the fraction of task-related and/or tuned cells, indicating that throughout the motor cortex, a large fraction of neurons (recorded from sites that controlled task-related as well as task-unrelated joints) exhibited comparable task-related activity. This pattern is consistent with the “dense” coding scheme employed in motor and premotor areas [33, 34], where many cells exhibit task related activity. This is a very different operational principle than the sparse coding scheme often ascribed to sensory cortical areas [35, 36].…”
Section: Discussionsupporting
confidence: 83%
“…The changes in motor cortical maps were not accompanied by corresponding changes in the fraction of task-related and/or tuned cells, indicating that throughout the motor cortex, a large fraction of neurons (recorded from sites that controlled task-related as well as task-unrelated joints) exhibited comparable task-related activity. This pattern is consistent with the “dense” coding scheme employed in motor and premotor areas [33, 34], where many cells exhibit task related activity. This is a very different operational principle than the sparse coding scheme often ascribed to sensory cortical areas [35, 36].…”
Section: Discussionsupporting
confidence: 83%
“…Condition-independent neural activity previously has been observed in motor tasks that are overtrained to be consistent across trials (Kaufman et al, 2016;Kobak et al, 2016;Rouse and Schieber, 2018). Here, in a precision center-out task with considerable trial-to-trial variability, the conditionindependent neural dynamics were observed to be similar for both initial as well as corrective movements and were cyclic.…”
Section: Similar But Smaller Condition-independent Activity For Corresupporting
confidence: 53%
“…In addition to encoded movement features, however, there is also a large condition-independent component in the firing rate of neurons in motor cortex (Kaufman et al, 2016;Rouse and Schieber, 2018). Condition-independent neural activity is the change in a neuron's firing rate from baseline that happens regardless of the instructed movement for any given trial within a given task.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility remains that dynamics are present in M1 during grasp, but that they are higherdimensional than during reach, or that they are nonlinear. Indeed, previous work analyzing neural state spaces in M1 during a reach-grasp-manipulate task found that neural activity is higher-dimensional than that observed during reach movements alone 6 . As a first test of these possibilities, we examined the relationship between movement and neural activity from the standpoint of decoding.…”
Section: Main Textmentioning
confidence: 99%